2019
DOI: 10.18551/rjoas.2019-01.18
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effectiveness of Sustainable Food House Area Program (Krpl) in Utilization of Yard Land in Banda Aceh

Abstract: The KRPL program is a breakthrough that could increase the ability of communities in terms of farming, food self-sufficiency in order to meet family food needs are diverse, nutritious and healthy and ensure continuity in terms of food supply that is safe for each individual. The implementation of the KRPL program in Banda Aceh City has 9 factors includes motivation, participation, land area, age, education, work background and also the community's perspective on the yard only on aesthetic value.From nine facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…relatively low. [7] The food pattern of household expectations It can be said that households participating in the P2L program generally still do not meet the national PPH value that has been set, because most households have a quality score that is still below the government's desire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…relatively low. [7] The food pattern of household expectations It can be said that households participating in the P2L program generally still do not meet the national PPH value that has been set, because most households have a quality score that is still below the government's desire.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are 47 groups of gampongs/villages participating in this program for a period of 9 (nine) years. As previous research that has been carried out [7] it is stated that in fact what has been done by the Government in this P2L program in this case agricultural extension workers socialization to the community is correct and has followed the existing technical instructions that have been set, but due to lack of understanding of community characteristics in determining program targets for the implementation of this P2L activity made this activity ineffective. There is a strong suspicion that the community is not from a farming background, has their own business or has limited time, including other things related to land characteristics, age, education, occupation and lack of motivation and participation in farming.…”
Section: Introductionmentioning
confidence: 99%
“…The data showed that the higher the understanding of the P2L program (objectives, scope, funding sources, and program organizational structure) did not determine the participation in the P2L program. According to the research [4], of which nine factors are suspected to affect the effectiveness of the KRPL program in Banda Aceh, three factors that significantly affect the increase in the effectiveness of the KRP program need to be improved, namely the motivation factor to the community, technology for optimizing the use of yard land, and the intensity of counselling/assistance.…”
Section: Resultsmentioning
confidence: 99%
“…Yard optimization activities with the KRPL / P2L method are one of the activities that can be carried out during the COVID-19 pandemic to prevent food shortages at the household level [3]. The KRPL program is an effort by the government to improve the ability of the community in agricultural activities, food self-sufficiency to meet the diverse, nutritious and healthy food needs of families, and ensure sustainability in providing safe food for each individual [4]. The fulfilment of family food from using yard land through the KRPL / P2L program is very appropriate if it is carried out sustainably.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, for formal rules, there must be groups and legal entities or parties from the village government (gapoktan). Whereas in the LDPM, there are several agreements agreed and depending on the gapoktan group, using a system same as the cooperative's; every member who borrows seed from a barn must return it in excess according to the agreement agreed upon by the members at the meeting, and each gapoktan has different regulations (Mahrunnisa et al, 2019).…”
Section: Ldpm Program For Community Food Distribution Institutionsmentioning
confidence: 99%